Strategi Meningkatkan Kemampuan Bahasa Inggris Anggota E-COMER Melalui Program English Camp Berbasis Digital - Yahrif, Muhammad; Syukur, Ahmad; Yusuf, Deddy (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2025)
English language skills are an important requirement for E-COMER members in facing global competition. This PKM aims to improve the English language skills of E-COMER members through the implementation of a digital-based English Camp program. The implementation method is by implementing several interactive digital platforms, such as the Youtube application, Dualingo and Blogging, and learning videos (job interview simulations using English). The results of the PKM show that the digital-based approach can significantly increase the learning motivation of E-COMER members due to the flexibility of time and accessibility. In addition, participants felt a significant increase in their active communication skills in English, especially through conversation simulation sessions using video calls. Key factors for the success of the program include technological support, this PKM recommends that similar programs be implemented sustainably with the development of adaptive features to support individual learning needs. Thus, a digital-based English Camp can be an effective solution in improving the English language skills of E-COMER members, while preparing them to face the challenges of globalization.